The customization of science : the impact of religious and political worldviews on contemporary science / edited by Steve Fuller, University of Warwick, UK, Mikael Stenmark, Uppsala University, Sweden, Ulf Zackariasson, Uppsala University, Sweden. - Fuller, Steve, 1959-; Stenmark, Mikael; Zackariasson, Ulf, 1970- (Palgrave Macmillan, 2014)
"This book explores whether and how religious and secular worldviews and political ideologies held by scientists, citizens, decision-makers and politicians influence science as practiced and understood today. In this book, customized science is defined as a science built according to - or altered and fitted to - a particular group's specifications, that is, its needs, interests or values, its political ideology or worldview. It is science governed not merely by goals such as increased knowledge and explanatory power, but also by goals such as economic growth, sustainable development, the equality of women or the end of religion. The contributions to this book discuss, with regard to particular worldviews and themes connected to the public role of science, whether science is increasingly becoming customized to fit the needs and interests of various groups in society, but also what the consequences of such a development may be both for science and society"--